What Can Decolonisation of Curriculum Tell Us About Inclusive Assessment? - Lambert, Sarah; Funk, Johanna; Adam, Taskeen (Routledge)
This chapter presents a Culturally Inclusive Assessment model and examples developed from our work to address legacies of racist and sexist curriculum and experiences. By drawing on the theories and principles that have informed work on the cultural diversification of learning materials and online courses, we have identified opportunities for Culturally Inclusive Assessment tasks, feedback, and processes. Our interest is to re-imagine assessment through the lenses of anti-racism and decolonialisation to address how inclusive assessment can be developed to better meet the needs of contemporary higher education. Salient features of the current context include the socio-cultural diversity of the student cohort and a desire for internationalising the curriculum, both of which have never been more pertinent. The chapter also provides stimulus questions based on the Culturally Inclusive Assessment model to help readers develop their own more culturally inclusive units, curriculum and assessments based on decolonising the content, the learning processes or pedagogy as a whole.